Implementing prosumers into heating networks. (1st September 2021) - Gross, Michel; Karbasi, Babak; Reiners, Tobias; Altieri, Lisa; Wagner, Hermann-Josef; Bertsch, Valentin
Abstract: This article investigates possibilities for including prosumer structures in heating networks. Therefore, the performance of three different heating system scenarios for a new housing district is investigated. Low (60 °C) and ultra-low (20 °C) network temperatures are investigated. The case study includes about 100 different single-family and multi-family houses. Two scenarios contain networks with temperatures of 20 and 60 °C. The third scenario is extended with solar collectors and a supermarket as decentralised prosumers who supply heat to the network in times of surplus. The network can simulate bidirectional flows. Based on the principles of graph theory, a combined hydraulic and thermal model is developed and used for this study. The results show a heat loss reduction in ultra-low temperature networks due to lower network working temperatures (20 °C) of about 80% compared to a low-temperature network. The implementation of prosumers considerably reduces the demand from a central heat source. In this study, 20% of the total heating demand can be covered by excess heat of the prosumer supply. Highlights: Thermal-Hydraulic simulation based on Hardy-Cross-Method and Multipole-Method. Low-Temperature and Ultra-Low-Temperature networks in a real-world use case. Prosumers in heating networks i.e. solar thermal collectors and supermarkets. Prosumer can cover 20% of the overall heat demand.